ANALISIS DESAIN DAN KEKUATAN MATERIAL FIRE TRUCK WATER TANK KAPASITAS 800L DENGAN METODE COMPUTER AIDED ENGINEERING (CAE) - Lintang Riady Atmaja; Fuad Hilmy; Raka Mahendra Sulistiyo; Herru Santosa Budiono (ELEMEN : JURNAL TEKNIK MESIN, 2026)
The water tank is a critical component of a fire truck, serving as the main water reservoir during firefighting operations. Selecting the right design and material greatly affects the vehicle’s performance. This study evaluates the strength, safety, and efficiency of different water tank configurations using Computer-Aided Engineering (CAE) with SolidWorks software. Three design variations and two material types were analyzed. The simulations yielded a Von Mises stress of 36.232 MPa, displacement of 2.851 mm, a safety factor of 5.9, and a total tank weight of 60.896 kg. Among the tested configurations, Design Model 3 demonstrated the best overall performance, offering optimal strength, safety, and material efficiency.